Comparative study on nutritional compositions and pathogenic microorganism isolated from green turtle egg and chicken egg - Katni, Nor Hashikin; F. M. A., Amirul; A. A., Affan; A. A. A., Ghani; Tengku Azizan, Tengku Rinalfi Putra; Zakaria, Zunita; Che' Amat, Azlan; Abu Hassim, Hasliza (Science and Education Publishing, 2021)
Exploitation of marine turtles is getting more severe as their population is starting to decline by years. The consumption of their eggs by the public is one of the factors that lead to this matter. However, there is not much research done so far on its nutritional composition and how it affects public health. A comparative study between turtle egg and chicken egg was done to evaluate the egg’s nutrient content and pathogenic microorganism. A total of 30 turtle eggs were purchased from the wet market located in Terengganu to determine the percentage of fatty acid and crude protein within the eggs. There was no significant difference between the crude protein percentage in chicken and turtle eggs; 11.99% and 11.58%. In this study, the composition of fatty acids, Omega-3 (N3PUFA) and Omega-6 polyunsaturated (N6PUFA), monounsaturated (MUFA), and saturated fatty acids (SFA) were determined. From the findings, there was a significant difference in saturated and monounsaturated fatty acids where the composition was higher in turtle eggs (35.27% and 48.79%, respectively) as compared to chicken eggs (31.99% and 45.3%, respectively). On the other hand, turtle eggs were higher in Omega-3 but lower in Omega-6 FAs (13.35%, 2.58%), which contrary to the chicken eggs (6.44%, 16.27%). In bacterial isolation, none of the isolates were positive for Salmonella sp. and the majority of the isolates were positive with Proteus mirabilis in both chicken and turtle eggs. The presence of this bacteria in turtle eggs might pose certain health risks as they are commonly consumed raw by the public. In conclusion, these findings related to the composition of fatty acid, protein and the existence of bacteria in the turtle egg would allow us to increase the conservation effort to keep the population from extinction.